Tourism climate insurance: implications and prospects - Olya, Hossein G. T.; Alipour, Habib; Peyravi, Bahman; Dalir, Sara (Routledge Journals, Taylor & Francis Ltd, 2019)
This paper investigates the intentions of tourists to purchase climate insurance as part of their holiday packages. A research model, based on Bagozzi's reformulation of attitude theory designed to examine the relationships between climate expectation-disconfirmation and the behavioral intentions of tourists in purchasing tourism climate insurance, with destination loyalty as an outcome. The model hypothesizes and tests whether expectation-disconfirmation can be resolved by insuring the product-climate. A structural equation modeling is utilized. The results reveal that the expectation-disconfirmation of tourists in relation to climate is positively associated with their intentions to purchase insurance and negatively affects loyalty.
Keywords: Tourism climate insurance; expectation-disconfirmation; climate change; loyalty; seasonality; North Cyprus; Purchase intention; Mediterranean; Reformulation of attitude theory; Destination management